SCREENING PANELIS INTERNAL DI PT FOODEX INTI INGREDIENTS: Internal Panelist Screening at PT Foodex Inti Ingredients - Sabna Sabilla Adera; Neny Mariyani; Fifi Fitria Eddy (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2022)
Internal panelist screening is a selection activity for a panelist who can recognize and have good sensory attribute sensitivity. This study aims to obtain internal panelists with a minimal category as moderately trained panelists, who will then be used as panelists for the differentiation test. Screening panelists at PT Foodex Inti Ingredients were carried out by conducting several sensory sensitivity tests, namely basic taste identification test, basic taste intensity test, aroma identification test, and flavor identification test. The screening internal panelist was attended by 14 participants from several different departments. Participants must be able to meet the requirements that have been set to become panelists, these requirements are: (1) to have a 100% correct score on the identification and basic taste intensity test, and (2) to have a minimum score of 70% of the overall score. Based on the tests, 5 participants managed to become internal panelists at PT Foodex Inti Ingredients. These five internal panelists will join other internal panelists and be used as a panelist in the differentiation test. Participants who do not pass are allowed to join the internal panelist screening in the next period. ABSTRAKScreening panelis internal merupakan kegiatan seleksi panelis internal yang mampu mengenali dan memiliki kepekaan atribut sensori dengan baik. Tujuan dari studi ini adalah untuk mendapatkan Screening panelis di PT Foodex inti Ingredients dilakukan dengan melakukan beberapa uji kepekaan sensori yaitu uji identifikasi rasa dasar, uji intensitas rasa dasar, uji identifikasi aroma, dan uji identifikasi flavor. Kegiatan screening panelis internal diikuti oleh 14 peserta yang berasal dari beberapa departemen berbeda. Peserta harus dapat memenuhi syarat yang telah ditetapkan untuk menjadi panelis, syarat tersebut yaitu: (1) memiliki nilai benar 100 % pada uji identifikasi dan intensitas rasa dasar, dan (2) memiliki nilai minimal 70 % dari nilai keseluruhan. Berdasarkan uji yang telah dilakukan, didapatkan 5 peserta yang berhasil menjadi panelis internal di PT Foodex Inti Ingredients. Kelima panelis internal ini akan bergabung dengan panelis internal lainnya dan digunakan sebagai panelis pada uji pembedaan, sedangkan peserta yang tidak lolos diberikan kesempatan untuk melakukan screening panelis internal di periode selanjutnya.